2006
DOI: 10.1007/s00414-006-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Nanotrap Sg as a semen detection kit before male-specific DNA profiling in sexual assaults

Abstract: A commercially available semen detection kit, Nanotrap Sg, which employs a one-step detection test based on immunochromatographic assay for the semenogelin protein, was evaluated for profiling male-specific DNA in sexual assault casework samples. While semen diluted with phosphate-buffered saline held and kept at 4 degrees C for 1 week showed a relatively strong signal intensity with Nanotrap Sg, the signal intensity was decreased by dilution after storage at 4 degrees C or freezing and thawing repeated more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
3
18
0
2
Order By: Relevance
“…The sensitivity of the ABAcard p30 Test was tested slightly better in this study than the value claimed by the manufacturer and was comparable to the reported sensitivity of two other PSA detection kits, Seratec PSA Semiquant and PSAcheck-1 [7]. The sensitivity of the RSID-Semen Test was equivalent to that of another recently commercialized Sg detection kit called Nanotrap Sg [20]. With both tests capable of detecting the human semen and the seminal fluid standard at 50,000-fold dilution, they are considered offering highly sensitive tests for the detection of semen.…”
Section: Sensitivitysupporting
confidence: 64%
“…The sensitivity of the ABAcard p30 Test was tested slightly better in this study than the value claimed by the manufacturer and was comparable to the reported sensitivity of two other PSA detection kits, Seratec PSA Semiquant and PSAcheck-1 [7]. The sensitivity of the RSID-Semen Test was equivalent to that of another recently commercialized Sg detection kit called Nanotrap Sg [20]. With both tests capable of detecting the human semen and the seminal fluid standard at 50,000-fold dilution, they are considered offering highly sensitive tests for the detection of semen.…”
Section: Sensitivitysupporting
confidence: 64%
“…The minimal concentration here was 1.77 ng PSA/ml. The semelogelin test, which is said to have a higher sensitivity than the PSA test, was recently introduced as a further preliminary test for sperm [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The slides are then normally kernechtrot picroindigocarmine (KPIC) stained and examined for sperm cells using brightfield microscopy. The microscopy provides a rapid answer to whether or not the sample is likely to contain enough DNA for profiling and is one of the traditionally used methods together with prostate specific antigen, seminal acid phosphatase and semenogelin measurements for indication of semen or seminal fluids in the sample [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%